COLLABORATIVE GOVERNANCE DALAM PEMBANGUNAN SISTEM PENGAIRAN PEDESAAN DI DESA BAKTI AGUNG KECAMATAN POSO PESISIR UTARA - rifai, ahmad; Hattab, Syahruddin; Astuti, Agusta Sri (JPS: Journal of Publicness Studies, 2025)
Collaborative governance is a method of governance that directly involves stakeholders outside the government or state, oriented towards consensus and deliberation in the collective decision-making process aimed at creating or implementing public policies and public programs. This research aims to understand how community involvement in collaborative governance can contribute to the development of the water system in Bakti Agung Village, North Poso Coastal Region. This study employs a qualitative descriptive approach and utilizes purposive sampling techniques. Data collection methods include observation, interviews, literature study, and documentation. To gather data, this research involves five informants. The theory used is Ratner's (2012), which includes three indicators: Identification of Barriers and Opportunities, Debate Strategies to Influence, and Planning Collaborative Actions. The results of this study indicate that the poor rural irrigation system is caused by inadequate identification of obstacles and opportunities. Communication between the community and the government regarding the repair of damaged dams is still not well-established. Decision- making needs to be carefully considered in the collaboration process to address the needs and problems faced by farmers. To prevent recurring damage, a routine maintenance system is necessary to ensure the irrigation system is well-maintained. Improvements in irrigation infrastructure must include better and cleaner channels to reduce the risk of blockages due to waste and sedimentation.